PENGARUH TERPAAN PERINGATAN KESEHATAN BERGAMBAR PADA KEMASAN PRODUK ROKOK TERHADAP PERILAKU BERHENTI MEROKOK : Studi Pada Mahasiswa Perokok Di FISIP UPNVJ - Laksana Aprilanda (2021)
Smoking is one of the global problems. Paper cylinders containing tobacco and other materials are one of the biggest contributors to death in Indonesia. In response to these problems, the government established Regulation of the Minister of Health of the Republic of Indonesia No. 28 of 2013. Regarding the inclusion of health warnings and health information on tobacco product packaging. But the policy, there are still many smokers who roam the streets even in public places. Cigarettes are also consumed by young people such as students and college students. Students should have sufficient capacity to be aware of the dangers posed by cigarettes through policies that have been implemented. The purpose of the study was to determine whether there was an effect and the magnitude of the effect resulting from the exposure of pictorial health warnings on cigarette product packaging on smoking cessation behavior in student smokers at FISIP UPNVJ. The theory used is the Protection Motivation Theory (PMT). The method used is a quantitative method with the type of explanatory research. The population used was 100 smoking students at FISIP UPNVJ taken through non-probability sampling and purposive sampling techniques. The results of this study indicate that Ho is rejected and Ha is accepted, which means that there is an effect of exposure to pictorial health warnings on cigarette product packaging on smoking cessation behavior of FISIP UPNVJ students.